PENGGUNAAN MEDIA PLASTISIN UNTUK MENINGKATAN KEMAMPUAN KOGNITIF MENGENAL ANGKA PADA ANAK KELOMPOK KELAS A DI TK ADINDA SURABAYA - Yayuk Setyawati (MOTORIC, 2023)
One of the results of children's cognitive development is the ability to think symbolically, including the ability to recognize number symbols. Problems were found related to understanding the concept of numbers or symbols of numbers in class A group children at Adinda Sidosermo Kindergarten, Wonocolo District, Surabaya City, namely children who could only memorize arithmetic but were unable to pronounce the concept of numbers or number symbols. Therefore, research is needed to obtain learning strategies in the form of introducing the concept of numbers 1-10 through plasticine games, which are beneficial for children's motor, cognitive and patient development. The aim of the study was to describe the use of plastic media to improve the memorization of numbers and writing of 1-10 Kindergarten A children in Adinda Kindergarten Surabaya. plastic media to improve writing numbers 1-10 Kindergarten A children at Kindergarten Adinda Surabaya.The research used is qualitative research. The result is Learning to introduce the concept of numbers 1-10 through plasticine games, memorization and writing for group A, learning materials adapted to the level of ability of children in each study group, creating a harmonious relationship between the teacher and students by giving praise, applause and thanks. if the child follows the lesson well. The use of plasticine media does not experience obstacles. The response to the introduction of the concept of numbers 1-10 through plasticine games is that children easily remember the shape of the number concept, children are able to sort numbers from 1-10 and vice versa.Keywords: plasticine, cognitive, numbers